2020
DOI: 10.1002/ejhf.1990
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in COVID‐19 patients: prevalence, incidence and prognostic implications

Abstract: Aims Data regarding impact of COVID‐19 in chronic heart failure (CHF) patients and its potential to trigger acute heart failure (AHF) is lacking. The aim of this work was to study characteristics, cardiovascular outcomes and mortality in patients with confirmed COVID‐19 infection and prior diagnosis of HF. Also, to identify predictors and prognostic implications for AHF decompensations during hospital admission and to determine whether there was a correlation between withdrawal of HF guideline‐dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
236
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(291 citation statements)
references
References 32 publications
19
236
1
11
Order By: Relevance
“…Our results showed that 30-day mortality in CHF patients was remarkably high, almost double in comparison with non-CHF patients (51.2% vs. 29.1%). Similar mortality rate (40 to 63%) has been described in other series [ 11 , 12 , 13 , 14 ], which reflects the extremely poor prognosis in this population. The presence of CHF was independently associated with all-cause death in our cohort (HR 2.3 CI95% (1.26–4.2), p = 0.007), confirming similar results recently published by Álvarez et al [ 11 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results showed that 30-day mortality in CHF patients was remarkably high, almost double in comparison with non-CHF patients (51.2% vs. 29.1%). Similar mortality rate (40 to 63%) has been described in other series [ 11 , 12 , 13 , 14 ], which reflects the extremely poor prognosis in this population. The presence of CHF was independently associated with all-cause death in our cohort (HR 2.3 CI95% (1.26–4.2), p = 0.007), confirming similar results recently published by Álvarez et al [ 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…Notably, given the epidemiological relevance of CHF [ 16 ], few studies have analyzed the prevalence and prognosis of CHF in patients with SARS-CoV-2 infection [ 11 , 12 ]. Prevalence of CHF in the setting of SARS-CoV-2 infection has been described to be between 4.1% to 36.5%, these differences might be due to the different populations analyzed [ 11 , 12 , 13 , 14 , 18 ]. Although this prevalence seems low, it is possible that CHF patients were especially careful in self-isolating due to their baseline high risk; thus, their risk of infection could be lower than in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an additional role of epicardial adipose tissue has been suggested. Directly related to the myocardium, it is a highly inflammatory depot with dense macrophage infiltrates, highly enriched in proinflammatory cytokines, such as IL-6, which could, at least partially, account for the excess of mortality and complications observed among obese patients [30], although atrial arrhythmias and previous HF have also been found to be the most powerful contributors to acute HF and mortality during hospitalization [31]. Overall, although the exact nature of cardiac involvement of COVID-19 infection remains to be determined, all the above mechanisms may all play a role and may overlap.…”
Section: Article Highlightsmentioning
confidence: 99%